(untitled) (LIS TODAY, 2025)
Information retrieval systems are designed to retrieve information from a database quickly and accurately. A multilevel hierarchy is a recursive process that consists of logically related levels with relation and is represented in a linear sequence. They are intricate among the parts of a whole, statistically or dynamically. This paper explores the significance of incorporating multilevel hierarchy systems in designing a thesaurus. It aims to enhance the efficiency and usability of the linguistic resources. Thesauri are crucial in information retrieval, establishing semantic relationships between words. Traditional thesauri have employed a single-level hierarchy, but recent advancements in information organization and retrieval call for more sophisticated structures to accommodate the complexities of language and user needs. This article presents the methodologies and benefits of designing thesauri with multilevel hierarchy systems, which not only enhance the efficiency and usability of linguistic resources but also significantly improve the accuracy and speed of information retrieval.